Asymptotes

Bolzano

New member
Determine asymptotes of the following function:
$f(x) = \frac{x - 2}{e^{1/x}}$I've managed to find the vertical asymptote [imath]x = 0[/imath], but I'm struggling with oblique one. It's equation is [imath]y = ax + b[/imath] and I calculated that [imath]a = 1[/imath] using formula
$a = \lim_{x \to \infty} \frac{f(x)}{x}$Now, I have a problem finding b. I used formula
$b = \lim_{x \to \infty} (f(x) - ax)$and got that
$b = \lim_{x \to \infty} \bigg(\frac{x - 2}{e^{1/x} } - x\bigg)$which I don't know how to solve.

P.S.
I don't speak English very well and it's my first time asking question here, so sorry if there are some mistakes.

Last edited:

blamocur

Full Member
I would replace 1/x with a new variable and use L'Hopital's rule.

• topsquark

Bolzano

New member
I would replace 1/x with a new variable and use L'Hopital's rule.
I'm not allowed to use L'Hopital's rule.

blamocur

Full Member
Even without L'Hopital's rule switching to a variable which tends to 0 seems to make it more manageable.

Bolzano

New member
Even without L'Hopital's rule switching to a variable which tends to 0 seems to make it more manageable.
I've tried that and still wasn't able do it. I always end up with [imath]\frac{0}{0}[/imath].

blamocur

Full Member
I've tried that and still wasn't able do it. I always end up with [imath]\frac{0}{0}[/imath].
Which methods for solving 0/0 type limits are you familiar with ?

blamocur

Full Member
After scratching my head for a while I could not come up with a proof that [imath]\lim\limits_{u\rightarrow 0} \frac{e^u-1}{u} = -1[/imath] without using either L'Hopital's rule or Tailor's series.

Bolzano

New member
After scratching my head for a while I could not come up with a proof that [imath]\lim\limits_{u\rightarrow 0} \frac{e^u-1}{u} = -1[/imath] without using either L'Hopital's rule or Tailor's series.
I solved it! Thank you for giving me an idea.

Here's how I proved that [imath]\lim_{x \to 0} \frac{e^x - 1}{x} = 1[/imath].

Let [imath]e^x - 1 = u \Leftrightarrow x = \ln(u + 1)[/imath]. Then
$\lim_{x \to 0} \frac{e^x - 1}{x} = \lim_{u \to 0} \frac{u}{\ln(u + 1)} = \lim_{u \to 0} \frac{1}{\frac{1}{u}\ln(u + 1)} = \lim_{u \to 0} \frac{1}{\ln(u + 1)^{1/u}} = \frac{1}{\ln e} = 1$

Last edited:
• topsquark and blamocur

Dr.Peterson

Elite Member
I solved it! Thank you for giving me an idea.

Here's how I proved that [imath]\lim_{x \to 0} \frac{e^x - 1}{x} = 1[/imath].

Let [imath]e^x - 1 = u \Leftrightarrow x = \ln(u + 1)[/imath]. Then
$\lim_{x \to 0} \frac{e^x - 1}{x} = \lim_{u \to 0} \frac{u}{\ln(u + 1)} = \lim_{u \to 0} \frac{1}{\frac{1}{u}\ln(u + 1)} = \lim_{u \to 0} \frac{1}{\ln(u + 1)^{1/u}} = \frac{1}{\ln e} = 1$
Another approach is just to recognize [imath]\lim_{x \to 0} \frac{e^x - 1}{x}[/imath] as the derivative of [imath]e^x[/imath] at [imath]x=0[/imath], assuming you've seen that.

• topsquark and blamocur

blamocur

Full Member
I solved it! Thank you for giving me an idea.

Here's how I proved that [imath]\lim_{x \to 0} \frac{e^x - 1}{x} = 1[/imath].

Let [imath]e^x - 1 = u \Leftrightarrow x = \ln(u + 1)[/imath]. Then
$\lim_{x \to 0} \frac{e^x - 1}{x} = \lim_{u \to 0} \frac{u}{\ln(u + 1)} = \lim_{u \to 0} \frac{1}{\frac{1}{u}\ln(u + 1)} = \lim_{u \to 0} \frac{1}{\ln(u + 1)^{1/u}} = \frac{1}{\ln e} = 1$